PRINCIPLES OF USER-CENTERED DESIGN (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
Good user interfaces are essential for any successful product. A process of the user interface creation is not available include in the algorithmic scheme. In this articles will formulate principles principles o f user-centered design, criteria o f ergonomics interfaces and efficient interface’s rules of project. These principles are based usability computer training courses.